ONLINE TEACHING ENGLISH (American Journal of Pedagogical and Educational Research, 2023)
In this article dedicates teaching English online methods and activities. Teaching English Online has become a sought after job as people from every nook and corner of the world want to communicate efficiently to be more marketable and amass more recognition. Therefore as an English Language teacher, you always have an opportunity to reach out to these eager students from the comfort of your home.